2010
DOI: 10.3340/jkns.2010.48.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development of Brain Abscess Caused by Streptococcus Pyogenes Following Penetrating Skull Injury via the Ethmoidal Sinus and Lamina Cribrosa

Abstract: Objective : Streptococcus pyogenes is a beta-hemolytic bacterium that belongs to Lancefield serogroup A, also known as group A streptococci (GAS). There have been five reported case in terms of PubMed-based search but no reported case of brain abscess caused by Streptococcus pyogenes as a result of penetrating skull injury. We present a patient who suffered from penetrating skull injury that resulted in a brain abscess caused by Streptococcus pyogenes. Methods : The patient was a 12-year-old boy who fell down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The possible toxic reaction of the highly sensitive internal tissue, ie, sinus mucosa, remains a concern. 26 Experimental results on mongrel dogs with artificial, surgically created, standardized dehiscence bone defects on the buccal side of the installed implants showed that cyanoacrylate-combined calcium phosphate can serve as scaffold and substitute for the barrier membrane during a guided bone regeneration procedure. 24 Safe aerostatic effects on the resected pulmonary parenchyma were presented in an experimental study on a pig's resected pulmonary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The possible toxic reaction of the highly sensitive internal tissue, ie, sinus mucosa, remains a concern. 26 Experimental results on mongrel dogs with artificial, surgically created, standardized dehiscence bone defects on the buccal side of the installed implants showed that cyanoacrylate-combined calcium phosphate can serve as scaffold and substitute for the barrier membrane during a guided bone regeneration procedure. 24 Safe aerostatic effects on the resected pulmonary parenchyma were presented in an experimental study on a pig's resected pulmonary tissue.…”
Section: Discussionmentioning
confidence: 99%